2013
DOI: 10.1002/asi.22909
|View full text |Cite
|
Sign up to set email alerts
|

Initialism disambiguation: Man versus machine

Abstract: Disambiguation of ambiguous initialisms and acronymsis critical to the proper understanding of various types of texts. A model that attempts to solve this has previously been presented. This model contained various baseline features, including contextual relationship features, statistical features, and language-specific features. The domain of Jewish law documents written in Hebrew and Aramaic is known to be rich in ambiguous abbreviations and therefore this model was implemented and applied over 2 separate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The third difference is that in Rabbinic documents, which are written in Hebrew and Aramaic, there is much more frequent use of abbreviations and acronyms than in regular Hebrew documents [15]. A study conducted by [16] demonstrated that the manual disambiguation of an acronym is an extremely time-consuming process, and it is a very difficult task even for a professional. For these reasons, keywords and keyphrases that appear in rabbinic responsa documents are much more difficult to extract than keywords and keyphrases in academic papers or any other English article.…”
Section: Introductionmentioning
confidence: 99%
“…The third difference is that in Rabbinic documents, which are written in Hebrew and Aramaic, there is much more frequent use of abbreviations and acronyms than in regular Hebrew documents [15]. A study conducted by [16] demonstrated that the manual disambiguation of an acronym is an extremely time-consuming process, and it is a very difficult task even for a professional. For these reasons, keywords and keyphrases that appear in rabbinic responsa documents are much more difficult to extract than keywords and keyphrases in academic papers or any other English article.…”
Section: Introductionmentioning
confidence: 99%
“…HaCohen-Kerner et al (2004) show that there are 40,000 abbreviations in Hebrew, compared to 17,000 in English. A study made in 2013 (HaCohen-Kerner et al, 2013) shows that the manual disambiguation of an acronym is a very time-consuming process, and it is a very difficult task even for a professional; (5) Hebrew is an ancient language; people have been speaking that language since the beginning of the 2nd millennium BCE. In Hebrew, there are written texts from two thousand years ago and more, most of them rabbinical (religious) texts (Mughaz, 2003;Mughaz et al, 2019aMughaz et al, , 2019b.…”
Section: Introductionmentioning
confidence: 99%